2013
DOI: 10.1016/j.jhin.2013.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic VSL#3 prevents antibiotic-associated diarrhoea in a double-blind, randomized, placebo-controlled clinical trial

Abstract: VSL#3 is associated with a significant reduction in the incidence of AAD in average-risk hospital inpatients exposed to systemic antibiotics. As the incidence of CDAD has fallen sharply, no cases of CDAD were found. Probiotic administration as prophylaxis for CDAD may not be indicated in average-risk hospital patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 16 publications
2
56
0
Order By: Relevance
“…Moreover, this dosage was shown to be optimal in previous mouse colitis studies (30,48). For humans, a daily average dosage 4 3 10 11 to 9 3 10 11 CFU is recommended for both dietary management and ulcerative colitis (49,50). This means that, corrected for body weight, the dosages are in the same order of magnitude.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, this dosage was shown to be optimal in previous mouse colitis studies (30,48). For humans, a daily average dosage 4 3 10 11 to 9 3 10 11 CFU is recommended for both dietary management and ulcerative colitis (49,50). This means that, corrected for body weight, the dosages are in the same order of magnitude.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, effects of probiotics have been examined in clinical studies for a number of gastrointestinal diseases. For instance, randomized trials suggest that co-administration of VSL#3, a probiotic compound consisting of eight different bacterial strains [21], or Saccharomyces boulardii [22] significantly decrease the incidence of antibiotics associated diarrhea (AAD). Moreover, episodes of infectious diarrhea in both adults and children can be shortened by the use of probiotics [23].…”
Section: Introductionmentioning
confidence: 99%
“…A 2013 RCT conducted in 229 adult inpatients showed that compared with placebo, administration of a VSL#3 mixture reduced the risk of antibiotic-associated diarrhea; however, the difference between groups was significant only in the per protocol analysis (11.4 vs. 0%, respectively; RR 0.04, 95% CI 0.00-0.59) and not in the intention-to-treat analysis (8.9 vs. 4.3%, respectively; RR 1.91, 95% CI 0.68-5.43) [45]. …”
Section: Bacterial Probioticsmentioning
confidence: 99%